2000
DOI: 10.1053/euhj.1999.1981
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and the severity of atherosclerosis in myocardial infarction patients with stable angina pectoris

Abstract: Background Recent findings provide evidence for the importance of inflammatory processes in the pathogenesis of atherosclerosis. C-reactive protein was elevated in patients with peripheral artery disease, coronary heart disease and myocardial infarction compared to normal subjects. MethodsIn 1112 male and 299 female survivors of myocardial infarction (mean age SD, men, 50·4 9·5, women, 56·1 9·3), we investigated whether plasma C-reactive protein concentration is associated with the severity of coronary heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 30 publications
4
56
2
2
Order By: Relevance
“…To the best of our knowledge, there are no previous studies correlating hs-CRP with Syntax score in STEMI. However, a few studies have correlated it with the presence and extent of severity of CAD in ACS; the present study findings corroborate earlier studies, which have shown a correlation between CRP and the severity of CAD (29,30).…”
Section: Hs-crp (Mg/dl) Hs-trop T (Ng/ml) ---------------------------supporting
confidence: 83%
“…To the best of our knowledge, there are no previous studies correlating hs-CRP with Syntax score in STEMI. However, a few studies have correlated it with the presence and extent of severity of CAD in ACS; the present study findings corroborate earlier studies, which have shown a correlation between CRP and the severity of CAD (29,30).…”
Section: Hs-crp (Mg/dl) Hs-trop T (Ng/ml) ---------------------------supporting
confidence: 83%
“…13,14 An association between CRP and the presence and number of stenosed coronary vessels has been documented in coronary atherosclerosis. [15][16][17][18][19][20] With respect to carotid atherosclerosis, 2 studies have shown a positive association between serum CRP levels and the presence of carotid plaques. 20,21 In the Bruneck Study (Willeit et al 21 ), a significant relationship between CRP and early nonstenotic atherosclerosis (Յ40% narrowing of the lumen) was restricted to univariate analysis.…”
mentioning
confidence: 99%
“…Despite evidence relating CRP-hs and CHD, the role of this protein in the development of a pathological state has not been completely established. Chronic elevation of the CRP-hs level is evident in individuals with cardiovascular disease risk factors, such as diabetes, smoking, obesity, hypertension and dyslipidemia [29][30][31] . In the current study, a significant and independent correlation was observed between the CRP-hs level and BMI, and the HDLcholesterol and CRP-hs levels were shown to be signif- …”
Section: Discussionmentioning
confidence: 99%